Flatwoods Citrus Best Management Practice: Minimizing Direct Deposition of Pesticides into Waterways - Chris Wilson; Brian Boman; Ed Stover; Janet Bargar; Jack Hebb (EDIS, 2006)
SL-235 is a 5-page illustrated fact sheet by Chris Wilson, Brian Boman, Ed Stover, Janet Bargar and Jack Hebb. This document summarizes the results from a study evaluating the effectiveness of turning sprayer nozzles off at row ends as a proposed best management practice for preventing non-target deposition of pesticides in surface water connections such as irrigation and drainage ditches. It also estimates direct deposition on ground surfaces that translate into wasted product, as well as another potential source of surface water contamination through surface water runoff. Includes references. Published by the UF Department of Soil and Water Sciences, March 2006.